Morphological remarks on the peppermint shrimp Lysmata ankeri (Decapoda, Hippolytidae): implications for species identification of the L. wurdemanni complex - Alves,Douglas Fernandes Rodrigues (2015)
ABSTRACTThis contribution reviews the morphology and the main diagnostic characters of the peppermint shrimp Lysmata ankeri. Individuals were sampled by scuba divers from August 2008 to June 2013 on the subtidal rocky bottom at Couves Island, on the coast of São Paulo State, Brazil. In the laboratory, the individuals were analyzed morphologically, with emphasis on the characters used in the diagnosis of the species; measured as carapace length (CL); and photographed. Seventeen individuals of L. ankeri were analyzed with an average size of 6.9 ± 2.0 mm CL. From the morphological analysis the following variations of the diagnosis were observed: five teeth on the dorsal margin of the rostrum, in the diagnosis this was 6-8; five spines on the flexor margin of the dactyli of pereiopods 2-4, in the diagnosis this was 3-4. The records of this study extend the knowledge of the variation of some morphological characteristics for this species, resulting in an overlap among the species of the Lysmata wurdemanni complex.